Optimal Single-Walled Carbon Nanotube Vessels for Short-Term Reversible Storage of Carbon Dioxide at Ambient Temperatures - Kowalczyk, Piotr; Furmaniak, S.; Gauden, P.; Terzyk, A. (American Chemical Society, 2010)
Optimized light vessels composed of single-walled carbon nanotubes have high gravimetric and volumetric capacity for short-term reversible storage of CO2 at 298 K and near-ambient operating pressures. We use grand canonical Monte Carlo simulation for modeling of CO2 adsorption at 298 K and pressures up to 5.7 MPa. It is shown that both gravimetric and volumetric uptake of CO2 strongly depend on the pore size in nanotubes but not on their chiral vector. Moreover, for any operating storage pressure, a unique optimal size of carbon nanotubes is well-defined. At 1.5 MPa, the most efficient nanotubes that maximize both gravimetric and volumetric uptake of CO2 (i.e., 13.6 mmol g-1 and 11.4 mol dm-3) have diameters of 3.8 nm. This size corresponds to the (28,28) armchair nanotubes.We demonstrate that to make an objective statement about the efficiency of CO2 storage in any nanoporous material, the complete volumetric and gravimetric adsorption data are necessary. Taking this into account, we discuss the recently reported exceptionally high capacity of metal-organic frameworks. We show that MOF-177, known as the most efficient porous material for storage of CO2 at room temperature, is characterized by very high gravimetric uptake of CO2 (i.e., 21.8 mmol g-1 at 1.5 MPa and 33.5 mmol g-1 at 3.5 MPa). However, the reported volumetric density of CO2 adsorbed in MOF-177 at 298 K (i.e., 8.17 mol dm-3 at 1.5 MPa and 12.26 mol dm-3 at 3.5 MPa) is lower in comparison to storage vessels composed of optimized single-walled carbon nanotubes. Our systematic study of CO2 adsorption in bundles composed of singe-walled carbon nanotubes at 298 K indicates the potential of nanotubes for innovation in clean technologies.